Memantine prevents memory consolidation failure induced by soluble beta amyloid in rats - Tucci, Paolo; Mhillaj, Emanuela; Morgese, Maria Grazia; Colaianna, Marilena; Zotti, Margherita; Schiavone, Stefania; Cicerale, Maria; Trezza, Viviana; Campolongo, Patrizia; Cuomo, Vincenzo; Trabace, Luigia (Frontiers in Behavioral Neuroscience, 2014)
It has been well documented that β-amyloid peptide accumulation and aggregation in the brain plays a crucial role in the pathophysiology of Alzheimer’s disease (AD). However, a new orientation of the amyloid cascade hypothesis has evidenced that soluble forms of the peptide (sAβ) are involved in Aβ-induced cognitive impairment and cause rapid disruption of the synaptic mechanisms underlying memory. The primary aim of this study was to elucidate the effects of sAβ, acutely injected intracerebrally (i.c.v., 4 µM), on the short term and long term memory of young adult male rats, by using the novel object recognition task. Glutamatergic receptors have been proposed as mediating the effect of Aβ on synaptic plasticity and memory. Thus, we also investigated the effects of sAβ on prefrontal cortex (PFC) glutamate release and the specific contribution of N-methyl-D-aspartate (NMDA) receptor modulation to the effects of sAβ administration on the cognitive parameters evaluated. We found that a single i.c.v. injection of sAβ 2h before testing did not alter the ability of rats to differentiate between a familiar and a novel object, in a short term memory test, while it was able to negatively affect consolidation/retrieval of long term memory. Moreover, a significant increase of glutamate levels was found in PFC of rats treated with the peptide 2 h earlier. Interestingly, memory deficit induced by sAβ was reversed by a NMDA-receptor antagonist, memantine (5 mg/kg i.p), administered immediately after the familiarization trial (T1). On the contrary, memantine administered 30 min before T1 trial, was not able to rescue long term memory impairment. Taken together, our results suggest that an acute i.c.v. injection of sAβ peptide interferes with the consolidation/retrieval of long term memory. Moreover, such sAβ-induced effect indicates the involvement of glutamatergic system, proposing that NMDA receptor inhibition might prevent or lead to the recovery of early cognitive impairment.